Analysis Of The Influence Of Teachers' Communication Style On Students' Learning Motivation In The Online Teaching-Learning Activities - Muhamad Rif'an; Sagaf S. Pettalongi; Sumartira Sumartira; Yuli Martuti; Andi Fitriani Djollong (Journal on Education, 2024)
The purpose of this study is to determine how teacher communication techniques affect students' motivation to learn during the online learning process. The paradigm used in this study is post-positivist. This study employs qualitative methods using an explanatory case study approach, specifically in the context of descriptive qualitative research. In this study, purposive sampling is employed. Interviewing and documentation approaches are used in this study. Construct validity data analysis is used in this study. During the online learning process, the teacher's communication strategy changes to increase student motivation. Teachers apply different teaching methods, such as dubbing assignments, learning videos before class starts, and assignments to make video projects. However, despite these changes, student learning motivation tends to stagnate, with students only responding to what the teacher says without significant improvement. Although the communication strategies implemented by teachers are educational. The proposed redundancy communication strategy may be more effective for significantly increasing students' learning motivation in the online learning context.